PENGARUH MIKORIZA INDIGENOUS GULMA TERHADAP KERAPATAN GULMA PADA TANAMAN JAGUNG - Halim, Halim (Jurnal Agroteknos, 2011)
The research on the effet of mycorrhiza indigenous of weed to weed density   has carried out at Jatinangor West Java on August untill November 20008. The statistical method used in the this research was randomized block design with three replications. The research showed that important value of broads leaves at tillage are Lantana camara (L.) as 2,93 %, Mimosa pudica (L.) as 2,50 %, Ricinus communis (L.) as 2,46 %), Solanum torvum SW as 2,46 %, and Eupatorium odorata (L.) as 2,03 %. The important value of grasses are Imperata cylindrica (L.) Beauv as 1,61 % and Sacciolepis indica (L.) Chase as 1,47 %. Thus important value of sedges is Cyperus rotundus (L.) as 1,90 %. For 14 HST, important value of board leaves are Momordica charantia (L.) as 6,58 %, Ricinus communis (L.) as 3,62 %, Polygonumlongisetum De Br as 3,34 % and Ageratum conyzoides (L.) as 3,34 %. The important value of grasses are Eleusine indica (L.) Gaertn as 1,78 % dan Cynodon dactylon (L.) Pers as 1,37 %. Key words :   mycorrhiza indigenous, weed, important value, , grasses, sedges